(untitled) (International Journal of Communication Systems and Network Technologies, 2012)
In this paper an exhaustive investigation of existing image recognition techniques has been taken up. On the basis of various approaches and their performance criteria, it is proposed to use one of the available techniques with slight changes in the performance parameters. Also new hybrid mechanism for improving the performance of the existing feature extraction has been studied and investigated for furthering performance.